Constructed Polynomial Windows with High Attenuation of Sidelobes - Okarma, K. (Elektronika ir Elektrotechnika, 2013)
In the paper the idea of the constructed polynomial windows is presented together with the obtained results of their optimization towards low level of the sidelobes. The main advantages of the polynomial windows are their low computational complexity and ability to change their frequency properties by some modiﬁcations of the polynomial coefﬁcients in the time domain. Both of these merits are preserved in the constructed polynomial windows family discussed in the paper and the additional proﬁt is the possibility of using two lower order polynomials with additional switching operation with similar sidelobes’ attenuation as for higher order standard polynomial windows. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.4368